The Unidentified - Mariz, Rae. (New York : Balzer + Bray, 2010)
In a futuristic alternative school set in a shopping mall where video game-playing students are observed and used by corporate sponsors for market research, Katey "Kid" Dade struggles to figure out where she fits in and whether she even wants to.
Kirkus Review
Publisher's Weekly
Kirkus Review, September 2010
Publisher's Weekly, September 2010
Young Adult
Young Adult
Keywords: Alternative schools -- Juvenile fiction; Corporate sponsorship -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Schools -- Juvenile fiction; Alternative schools -- Fiction; Corporate sponsorship -- Fiction; Identity -- Fiction; Schools -- Fiction; Science fiction; Corporate sponsorship -- Fiction; Experimental schools -- Fiction; Individuality -- Fiction; School stories; Science fiction; Science fiction